TOURISM AND THE HINGGI DESIGN OF EAST SUMBA: A STUDY ON THE AESTHETICAL MORPHOLOGY OF COLORS AND MOTIFS OF TRADITIONAL CLOTHS - BIRANUL ANAS (Centre For Tourism Planning and Development, 2007)
In Indonesia, the tourism business, international tourism in particular, had been proceeding since the beginning of the 20th century and was increasingly confirming its existence during the period of the 1970-ies up to the 1990-ies due to the government planned development policy at that time. The development had impacted considerably on various sectors related to the country's culture, especially on the local people's traditional art in tourists receiving areas. Particular tourist destination areas have experienced certain changes in the orientation of production, from meeting the needs of internal cultures to serving the demands of external tourism established markets. This paper discusses the development of motifs of a specific traditional cloth produced by the East Sumba people in the years 1900